Leveraging Browser-Based Virtual Machines to Teach Operating System Fundamentals (Journal of The Colloquium for Information Systems Security Education, 2022)
In this paper, we identify challenges in delivering cybersecurity labs, including the overhead costs of delivering virtual machines to students. We propose instead to use JavaScript driven Browser-Based Virtual Machines (BBVMs) to overcome the challenges of Type I and II hypervisors, as well as vendor- specific cybersecurity lab ranges. BBVMs deliver configured VMs at lower cost to the student’s web browser and are much easier for students to use. BBVMs require no hardware or infrastructure for students besides an Internet-connected device. As such, labs delivery via BBVMs can be run on mobile phones, tablets, or computers with limited resources. With this in mind, the authors detail BBVM implementation for cybersecurity labs. With very little physical infrastructure, programming, and systems administration, an educational institution at any level may implement a cybersecurity lab in such an environment. Our examples focus on addressing learning the Linux command line, introducing different Linux commands, and deepen student understanding of the Linux operating system itself. We combine BBVMs with previous work to address configuration, repeatability, assessment, academic integrity/cheating, and other similar constraints using our polymorphic configuration methodology called PolyLab. Lastly, we include a step-by-step procedure to implement BBVMs and show use-cases for cybersecurity education.
Keywords: operating system; Linux; command line; education; virtual machines; cybersecurity